How mobile phone addiction is associated with suicidal ideation in university students in China: Roles of depression and online social support - Hu, Huahua; Yang, Xue; Mo, Phoenix K. H.; Zhao, Chengjia; Kuang, Beibei; Zhang, Guohua; Lin, Guangyao (Frontiers in Psychology, 2022)
Background Recent studies have highlighted mobile phone addiction (MPA) as a potential risk of suicidal ideation. However, the mechanisms underlying that association require attention. Objective This investigation aims to examine whether the relationship between MPA and suicidal ideation would be mediated by depression, and buffered by online social support (OSS) in university students. Methods A convenient sample of 1,042 Chinese university students completed the measures of mobile phone addiction, depression, suicidal ideation, OSS in classroom settings. Moderated mediation analyses were performed to test the roles of depression and OSS in the association between MPA and suicidal ideation. Results MPA was positively associated with suicidal ideation through depression (indirect effect =. 23, 95% CI: 0.18, 0.28, p < 0.001); OSS moderated the association between depression and suicidal ideation (B = − 0.09, 95% CI: −0.13, −0.04, p < 0.001). Specifically, the effect of depression on suicidal ideation was weaker in individuals with high (versus low) OSS. OSS moderated the association between MPA and suicidal ideation (B = 0.06, 95% CI: 0.02, 0.10, p = 0.001). The influence of MPA on suicidal ideation was non-significant among individuals with high OSS but negatively significant among students with low OSS. Conclusion The results enrich the understanding of how MPA may increase suicidal ideation, and highlight the potential importance of reducing depression and enhancing OSS to prevent suicidal ideation in university students.